Equity in the South African legal system a critical ethnography - Leiper, Jonathan (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2004)
This thesis focuses on the process of interpreting and the difficulties faced by interpreters in the Magistrates' Court in Grahamstown, South Africa. More particularly, the thesis seeks to establish whether the constitutional guarantee of language equity can be applied to the courts - given the numerous problems with interpreting. Respondents from different spheres of the legal profession were interviewed in order to ascertain their perspectives on the state of interpreting, problems that are encountered by interpreters and attitudes displayed by other members of the legal profession towards interpreters. The methodology used in the thesis is that of a critical ethnography. As such, the research also has a critical focus, seeking to determine the ideologies and interests of different ):articipants in the legal process. On the basis of the data collected, a number of conclusions are drawn. The first is that interpreting in South Africa is in trouble. The system of interpreting is beset by a number of different problems. This study describes four different types of problems that are faced by interpreters: linguistic problems, environmental problems, training and administrative issues, and poor status in the eyes of the other participants in the legal process. Together the cumulative effect of these problems is the undermining of the principle of equity in the justice system. Finally, the thesis provides various practical and achievable solutions to the problems outlined above, specifically those faced by interpreters. The researcher also critically evaluates the efforts and motives of the Department of Justice and Constitutional Development.
Keywords: Court interpreting and translating -- South Africa; Language and languages -- Law and legislation -- South Africa; Translators -- Training of -- South Africa; Translators -- Legal status, laws, etc. -- South Africa; Law -- Translating -- South Africa; Law -- South Africa -- Language